Mathematical frameworks for investigating fractional nonlinear coupled Korteweg-de Vries and Burger’s equations - Noor, Saima; Albalawi, Wedad; Shah, Rasool; Al-Sawalha, M. Mossa; Ismaeel, Sherif M. E. (Frontiers in Physics, 2024)
This article utilizes the Aboodh residual power series and Aboodh transform iteration methods to address fractional nonlinear systems. Based on these techniques, a system is introduced to achieve approximate solutions of fractional nonlinear Korteweg-de Vries (KdV) equations and coupled Burger's equations with initial conditions, which are developed by replacing some integer-order time derivatives by fractional derivatives. The fractional derivatives are described in the Caputo sense. As a result, the Aboodh residual power series and Aboodh transform iteration methods for integer-order partial differential equations may be easily used to generate explicit and numerical solutions to fractional partial differential equations. The results are determined as convergent series with easily computable components. The results of applying this process to the analyzed examples demonstrate that the new technique is very accurate and efficient.